Muslimah Creativity, Piety, and Solidarity in Mohja Kahf’s Hagar Poems - Djohar, Hasnul Insani; Oktaviano, Willy; Utami, Mira (NOBEL: Journal of Literature and Language Teaching, 2024)
This paper investigates how Kahf’s poetry collection, Hagar Poems (2016), discovers Muslim women or Muslimah leadership by exploring Muslimah leaders, such as Hagar (Hajar), Khadija, and Aisha to undermine reductionist views of Muslim women both in Orientalism and Anglo-American feminism. In doing so, Kahf uses the strategies of juxtaposition, humor, and irreverence by connecting Muslimah ancient leaders to her contemporary speakers who are crisscrossing Islamic traditions and American popular culture. By engaging with postcolonial and gender studies with the frameworks of leadership and Islamic studies, this paper investigates how Kahf’s women juxtapose ancient folkloric tales and American popular cultures, both to establish their multiple identities and leadership and to illuminate contemporary resonances of ancient Muslimah leaders in the eyes of subsequent generations. Indeed, the patterns of Muslimah leadership in Kahf’s poems are represented as engaging with the ideas of creativity, piety, and solidarity; and these patterns work to question the exclusion of Muslimah leadership in both gender and orientalist debates. Thus, Kahf’s Hagar Poems explores the representation of Muslim women from Islamic history who serve as role models, having displayed heroic characteristics through their leadership.